Interstitial Prostate Brachytherapy LDR-PDR-HDR - Kovc̀s, Gyr̲gy.; Hoskin, Peter. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Prostate brachytherapy has been the subject of heated debate among surgeons and the proponents of the various brachytherapy methods. This very first interdisciplinary book on the subject provides a comprehensive overview of innovations in low dose rate (LDR), high dose rate (HDR), and pulsed dose rate (PDR) interstitial brachytherapy for the management of local or locally advanced prostate cancer. In addition to detailed chapters on patient selection and the use of imaging in diagnostics, treatment guidance, and implantation control, background chapters are included on related medical physics issues such as treatment planning and quality assurance. The results obtained with the different treatment options and the difficult task of salvage treatment are fully discussed. All chapters have been written by internationally recognized experts in their fields who for more than a decade have formed the teaching staff responsible for the successful GEC-ESTRO/EAU Prostate Brachytherapy Teaching Course. This book will be invaluable in informing residents and others of the scientific background and potential of modern prostate brachytherapy. It will also prove a useful source of up-to-date information for those who specialize in prostate brachytherapy or intend to start an interstitial brachytherapy service.